Liquid biphasic flotation for the purification of C-phycocyanin from Spirulina platensis microalga - Chew, Kit Wayne; Chia, Shir Reen; Krishnamoorthy, Rambabu; Tao, Yang; Chu, Dinh-Toi; Show, Pau-Loke (Elsevier, 2019)
Liquid biphasic flotation (LBF), an integrated process of liquid biphasic system (LBS) and adsorptive bubbles flotation, was used for the purification of C-phycocyanin from S. platensis microalgae. Various experimental parameters such as type of phase forming polymer and salt, concentration of phase forming components, system pH, volume ratio, air flotation time and crude extract concentration were evaluated to maximise the C-phycocyanin recovery yield and purity. The optimal conditions for the LBF system achieving C-phycocyanin purification fold of 3.49 compared to 2.43 from the initial LBF conditions was in polyethylene glycol (PEG) 4000 and potassium phosphate combination, with 250 g/L of polymer and salt concentration each, volume ratio of 1:0.85, system pH of 7.0, air flotation duration of 7 min and phycocyanin crude extract concentration of 0.625 %w/w. The LBF has effectively enhanced the purification of C-phycocyanin in a cost effective and simple processing.